Larval abundance and spat collection of the lion’s paw scallop Nodipecten subnodosus in Ojo de Liebre Lagoon, Baja California Sur, Mexico - R Maguino-Napurí; AN Maeda-Martínez; T Moctezuma-Cano; G Valle-Meza; H Acosta-Salmón (Ciencias Marinas, 2010)
Large numbers of spat of giant lion’s paw scallop Nodipecten subnodosus are required for the development of the scallop aquaculture industry. Despite the large adult populations of this species in Ojo de Liebre Lagoon, Baja California Sur, Mexico, attempts to collect spat with onion bag collectors during the reproductive season (September–November) have not been successful. We assessed lion’s paw spatfall at three sites (La Ventana, El Conchalito, and El Borbollón) within the lagoon, where high recruitment was previously recorded. Netlon collectors instead of onion bags were used and they were deployed at each site at a depth of 1 m on two occasions (October and November 2007) when pediveliger larvae were more abundant. Collectors were retrieved and evaluated in February 2008, after being submerged for 118 or 82 days. Pediveliger larvae were present from late September to late November at all three sites. Densities peaked at 1 m in mid-November and were significantly higher at La Ventana, accounting for 12,400 larvae m–3. Collectors installed in October at El Conchalito showed higher (P < 0.05) mean recruitment (1.7 ± 0.2 spat per collector) than collectors set in November (0.4 ± 0.3 spat per collector). Collectors installed in October and November at La Ventana had 0.6 ± 0.3 and 0.9 ± 0.2 spat per collector, respectively. No significant differences were observed in the growth rates of the juveniles collected. High densities of larvae in the plankton during November indicated that high reproductive activity occurred earlier that month or in late October. La Ventana showed the highest potential for spat collection based on larval abundance, followed by El Borbollón and El Conchalito; however, El Conchalito showed the highest spat recruitment, followed by La Ventana and El Borbollón. Since spat collection was relatively low at all sites, more efforts to determine better collection sites and techniques, as well as appropriate deployment times are required.